Intermediary role performance analysis of Malaysian Islamic and conventional banks - Fauzias Mat Nor; Shaharuddin A.; Nawai N.; Marzuki A.; Zainuddin Wan Abdullah W. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by Scopus